2010
DOI: 10.1111/j.1742-7843.2010.00554.x
|View full text |Cite|
|
Sign up to set email alerts
|

Assessment and Characterization of Purinergic Contractions and Relaxations in the Rat Urinary Bladder

Abstract: The aim of the present study was to assess the purinoceptor functional responses of the urinary bladder by using isolated rat urinary bladder strip preparations. ATP elicited a transient bladder contraction followed by a sustained relaxation and ADP, UDP and UTP generated predominantly potent relaxations (relaxatory potencies: ADP = ATP > UDP = UTP). The ATP contractions were desensitized with the P2X 1 ⁄ 3 purinoceptor agonist ⁄ desensitizer a,b-meATP and reduced by the P2 purinoceptor antagonist PPADS but un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 57 publications
4
33
0
1
Order By: Relevance
“…Contractions Fig. 4 Original tracings showing the effects on the spontaneous mechanical activity of the longitudinal muscle of a mouse ileum induced by the P2Y 2 , P2Y 2 / 4 , and P2Y 6 receptor agonists, 2-thio-UTP, UTPγS, and PSB 0474 (10 μM each), respectively generated by UTP and UDP in ileum muscle are identical, indicating that the tissue responds similarly to UTP and UDP, as reported in rat mesenteric and basilar arteries [26,27] or in rat urinary bladder [28].…”
Section: Discussionmentioning
confidence: 74%
“…Contractions Fig. 4 Original tracings showing the effects on the spontaneous mechanical activity of the longitudinal muscle of a mouse ileum induced by the P2Y 2 , P2Y 2 / 4 , and P2Y 6 receptor agonists, 2-thio-UTP, UTPγS, and PSB 0474 (10 μM each), respectively generated by UTP and UDP in ileum muscle are identical, indicating that the tissue responds similarly to UTP and UDP, as reported in rat mesenteric and basilar arteries [26,27] or in rat urinary bladder [28].…”
Section: Discussionmentioning
confidence: 74%
“…α,β-meATP, an ATP analog, is a selective P2X receptor agonist and resistant to ATPase. Thus, repeated application of α,β-meATP can desensitize the P2X receptors (24,25). In the present study, the purinergic component was found to be as ~30% (field stimulation at 10 Hz) in the presence of PPADS and ~33% (field stimulation at 10 and 20 Hz) in response to desensitization with α,β-meATP both in the NC and the HC group out of ~60% atropine-resistant contractions.…”
Section: Discussionmentioning
confidence: 61%
“…P2X receptors (mainly P2X 1 ), expressed in mammalian bladders, are ATP-gated ion channels that contribute to urinary bladder functions (24,28). Several studies suggested that PPADS strongly suppresses P2X-purinoceptor-mediated contractions (25,31,32). α,β-meATP, an ATP analog, is a selective P2X receptor agonist and resistant to ATPase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ACh and ATP stimulate muscarinic and purinergic receptors of the smooth muscle, respectively, and elicit bladder contraction (Dowdall et al 1974;Kasakov and Burnstock 1982;Theobald and de Groat 1989). Although ATP plays an additional role in evoking the contraction of the detrusor in many species (rabbit, rat, mice;Calvert et al 2001;Aronsson et al 2010;Gomez-Pinilla et al 2011), it has little, if any, role in healthy human bladders (Sjogren et al 1982;Bayliss et al 1999). On the other hand, the proportion of atropine-resistant, nerve-mediated contractions in human bladders increases in several pathological conditions (interstitial cystitis, idiopathic detrusor overactivity, etc.…”
Section: Introductionmentioning
confidence: 99%